THE GROWING RELEVANCE OF THE CHINESE LANGUAGE IN UZBEKISTAN - Zongzheng Yuyan (International Journal of Literature and Language Studies, 2022)
In the modern era of globalization, foreign languages play a crucial role in shaping economic development, international cooperation, and cultural exchange. Uzbekistan, as a rapidly developing country in Central Asia, has increasingly recognized the importance of multilingualism. While English and Russian have traditionally dominated as foreign languages of communication, Chinese has recently gained significant attention. The rise of China as a global economic power and the strengthening bilateral relations between Uzbekistan and China have made the Chinese language highly relevant.